(untitled) (Al-Muthanna Journal of Sport Education Sciences, 2026)
Abstract This study aims to explore the impact of implementing an integrated teaching methodology based on the "Thinking Through Movement" philosophy on developing tactical performance (such as selecting the appropriate shot and constructing points) and mental competencies (such as decision-making speed and cognitive flexibility) among junior tennis players. The research’s significance lies in bridging the gap between isolated technical skills trained through traditional methods and the requirements of real, dynamic competition that demand tactical intelligence and high perceptual abilities. The study employed a quasi-experimental design with two groups (experimental and control) and pre-post testing on a sample of 20 junior players. The results showed a statistically significant improvement in the tactical and mental performance of the experimental group members who received the integrated program, compared to the control group. Analysis also revealed a very strong correlation between the criteria of the integrated methodology (such as motor-cognitive integration and intelligent constraint design) and both tactical and mental performance. The study concludes that the "Thinking Through Movement" methodology constitutes an effective framework for teaching tennis, transforming the court into a live laboratory for developing game intelligence through practicing skills in tactical contexts resembling reality. The researcher recommends adopting these integrated approaches in junior training, designing training activities based on modified games and problem-situations, and holding practical workshops for coaches to enable them to apply this modern philosophy.